j = 1 ∑ ∞ ( F j ) − 1 = ?
Notation: F n denotes the n th Fibonacci number . A Fibonacci number is a number of the sequence generated by F 0 = 0 , F 1 = 1 and F n = F n − 1 + F n − 2 for n ≥ 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
With ϕ = 2 1 ( 1 + 5 ) , we have F n = 5 1 ( ϕ n − ( − ϕ − 1 ) n ) , and hence F n 1 = ϕ n − ( − ϕ − 1 ) n 5 = ϕ n 5 ( 1 − ( − ϕ − 2 ) n ) − 1 = 5 k ≥ 0 ∑ ( − 1 ) k n ϕ − ( 2 k + 1 ) n so that n = 1 ∑ ∞ F n 1 = 5 k = 0 ∑ ∞ n = 1 ∑ ∞ ( − 1 ) k n ϕ − ( 2 k + 1 ) n = 5 k = 0 ∑ ∞ ϕ 2 k + 1 − ( − 1 ) k ( − 1 ) k This series is alternating, and its summands converge to 0 exponentially, so we have rapid convergence. The approximation 5 k = 0 ∑ 1 2 ϕ 2 k + 1 − ( − 1 ) k ( − 1 ) k ≈ 3 . 3 5 9 8 9 gives the sum to 5 DP accuracy.
Amazing! Brilliant solution. (+1)
Remark: You accidentally left out the term 5 here
n = 1 ∑ ∞ F n 1 = 5 k = 0 ∑ ∞ n = 1 ∑ ∞ ( − 1 ) k n ϕ − ( 2 k + 1 ) n = 5 k = 0 ∑ ∞ ϕ 2 k + 1 − ( − 1 ) k ( − 1 ) k
And finally
k = 0 ∑ 1 2 ϕ 2 k + 1 − ( − 1 ) k ( − 1 ) k ≈ 1 . 5 0 2 5 8 9 ⇕ 5 k = 0 ∑ 1 2 ϕ 2 k + 1 − ( − 1 ) k ( − 1 ) k ≈ 3 . 3 5 9 8 9
There was one more query, how did you get this?
ϕ n 5 ( 1 − ( − ϕ − 2 ) n ) − 1 = 5 k ≥ 0 ∑ ( − 1 ) k n ϕ − ( 2 k + 1 ) n
Problem Loading...
Note Loading...
Set Loading...
This is the Reciprocal Fibonacci Constant, and the closed form of this constant is
4 5 ( 2 L o g ( ϕ ) 1 ( L o g ( 5 ) + 2 ψ ϕ − 4 ( 1 ) − 4 ψ ϕ − 2 ( 1 ) ) + ( ϑ 2 ( 0 , ϕ − 2 ) ) 2 ) = 3 . 3 5 9 8 8 5 6 6 6 2 4 3 1 7 7 5 5 3 2 . . .
where ϕ is the golden ratio , ψ is the q-Polygamma function , and ϑ is the elliptic theta function
It's much easier to just add up the first 30 terms or so to get 5 decimal point accuracy.